THE EFFECT OF SOCIAL SUPPORT ON STUDENTS' ADAPTABILITY AND EMOTIONAL REGULATION IN THE SCHOOL ENVIRONMENT OF SMP NEGERI 19 MEDAN - Giawa, Febriani; Lubis, Indah Sari Liza; Fadhilah, Cut Rafiqa (Yayasan Amanah Nur Aman, 2025)
This study aims to determine the influence of partial social support on adaptability, determine the influence of social support on partial emotional regulation and determine the effect of simultaneous social support on students' adaptability and emotional regulation in the school environment of SMP N 19 Medan. This research was conducted at SMP N 19 Medan with a class VIII population of 225 students. The sampling technique in this study is probability sampling which provides the opportunity to be selected as a sample member of 69 students. The results of this study show that the value of the social support variable social support is 2.54 and the table value is 1.99, so it can be concluded that social support has a partial effect on adaptability. The effect of social support on the regulation of emotions as a result of the tcal value is 2.56 and the ttable value is 1.99, so it can be concluded that social support has a partial effect on the regulation of emotions. The adaptability variable (y1) of the determination test results showed an R square value of 0.088. This means that social support contributes 8.8% to the variation in respondents' adaptability, while 91.2% in the emotion regulation variable shows an R square value of 0.089. This means that social support contributes 8.9% to the variation in respondents' emotional regulation. While the rest were influenced by other variables that were not studied in this study.